Ardisia silamensis - Tsen, S.; Hor, C.S.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Ardisia silamensis is a small tree endemic to Sabah. It is only known from Mount Silam. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km2. The most plausible threats that could affect the population of this species are forest fire and climate change. If these were to occur, they could drastically change the conservation status to Critically Endangered or Extinct. Hence, it is assessed as Vulnerable. Ardisia silamensis is endemic to Sabah, Malaysia. It is confined to ultramafic substrate on Mount Silam, Lahad Datu.